2003
DOI: 10.2214/ajr.180.4.1801037
|View full text |Cite
|
Sign up to set email alerts
|

The Urethra and Its Supporting Structures in Women with Stress Urinary Incontinence: MR Imaging Using an Endovaginal Coil

Abstract: MR imaging with an endovaginal coil revealed significant morphologic alterations of the urethra and supporting structures in patients with stress urinary incontinence.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
43
0
1

Year Published

2004
2004
2021
2021

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 81 publications
(45 citation statements)
references
References 22 publications
1
43
0
1
Order By: Relevance
“…Others have shown that urethral sphincter area and circumference decrease as the severity of stress incontinence increases [26]. Another MRI study found that the urethral sphincter is thinner in incontinent women than in asymptomatic women [27].…”
Section: Discussionmentioning
confidence: 96%
“…Others have shown that urethral sphincter area and circumference decrease as the severity of stress incontinence increases [26]. Another MRI study found that the urethral sphincter is thinner in incontinent women than in asymptomatic women [27].…”
Section: Discussionmentioning
confidence: 96%
“…Overfat women have high values of intra-abdominal pressure [3] which may increase the intra-vesical pressure and urethral mobility, and affect pelvic floor muscles [3,32,33,35]. Another anatomical explanation would be the association between retropubic space and stress UI since overweight women have more retropubic space than their normal-weight counterparts [36]. Limited individual mobility and sedentarism may influence severity and type of UI [37].…”
Section: Discussionmentioning
confidence: 99%
“…Other pathological causes have been attributed to urethral hypermobility, intrinsic sphincter deficiency, or urethral trauma (e.g., resulting from childbearing, surgical trauma, prolonged increased abdominal pressure) [21][22][23]. Women suffering from SUI often fear urinary leakage and are therefore impaired in their social or physical activities [24].…”
Section: Anterior Compartmentmentioning
confidence: 99%